Language variation on Jamaican radio - Westphal, Michael, 1968- (Varieties of English around the world. General series ;, 2017)
"This volume presents an in-depth analysis of language variation on Jamaican radio newscasts and talk shows. It explores the interaction of global and local varieties of English with regard to newscasters' and talk show hosts' language use and listeners' attitudes. The book illustrates the benefits of an integrated approach to mass media: the analysis takes into account radio talk and the perception of the audience, it is context-sensitive, paying close attention to variation within and between genres, and it combines quantitative and qualitative approaches to demonstrate the complexity of language in the media. The book contributes to our understanding of the dynamics of World Englishes in the 21st century and endonormative stabilization processes in linguistically heterogeneous postcolonial speech communities, and shows how mass media both challenge and reproduce sociolinguistic stratification. This volume will be relevant for researchers interested in the fields of sociolinguistics, language attitudes, and language in the media"--